Recursos didácticos y su incidencia en el proceso enseñanza - aprendizaje en los estudiantes de la unidad educativa ab. Jaime Roldos Aguilera del cantón Montalvo Provincia de los Ríos en el año 2016 - Criollo Parco, Lida Marisol (2016)
The work entitled Physical activity and its impact on obesity among the inhabitants of Ximena 3 citadel of Babahoyo canton province Rivers, collects diagnostic results that reveal the situation presented by people in the industry with problems of obesity and lack of understanding of the risks representing the health, exploratory made it possible to know the activities that people do object of study and knowledge of obesity, as well as the willingness by the group observed to do some physical activity that may contribute to the improvement and maintenance of health. theoretical methods and empirical level of scientific research and mathematical and statistical methods were used. It is the opinion of this author that scientific result, be taken into account by the relevant authorities, can contribute to improve the preparation of teachers to address the decline of obesity.